Fundamentals and Main Provisions of the Functional-Procedural Concept of Mental Deprivation - Terletska, Yuliana M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Science still does not have a single scientifically sound concept of mental deprivation, which would explain its psychological essence, this mental phenomenon cannot be adequately assessed, or measures to prevent or eliminate negative mental phenomena it provoked cannot be developed. The article aims to reveal the basic principles and substantiate the main provisions of the functional-procedural concept of mental deprivation. Psycho-energetic and energy-psycho-functional approaches were used, as well as methods of analysis, synthesis, abstraction, specification, comparison, generalisation, and grouping of knowledge about the human psyche. The functional-procedural concept of mental deprivation of humans covers an interconnected system of provisions. According to them, mental deprivation is a course of more or less powerful destructive processes in the functioning of his psyche. Such processes arose from the destruction of mental parameters in various areas due to long-term unfulfilling necessary for normal functioning and development. The development of a functional-procedural concept of mental deprivation of a human will make it possible, first, to adequately define its essence and content in the scientific dimension as a phenomenon of the psyche; secondly, to assess its impact on the functioning of the whole psyche; third, to disclose the impact on development or its delay, actions, behaviour, and activities of an individual; fourth, to develop psychotherapeutic measures to prevent the occurrence of mental deprivation and eliminate its negative consequences.